2016
DOI: 10.3153/jfhs16009
|View full text |Cite
|
Sign up to set email alerts
|

ISOLATION OF Salmonella spp. AND OTHER MEMBERS OF Enterobacteriaceae FROM HORSE MACKEREL (Tra-churus trachurus), SOLD IN PUBLIC MARKETS OF ISTANBUL, TURKEY

Abstract: Abstract:Aim of this investigation is to provide the general information about prevalence of members of Enterobacteriaceae in horse mackerel (Trachurus trachurus) sold in open public markets in Istanbul, Turkey. Horse mackerel were randomly selected and collected in warm and cold seasons of the year. Purchased samples were kept in sterile insulated bags with ice and transported to the laboratory for microbiological analyses. Citrobacter spp. showed highest prevalence (45.56%), followed by Proteus mirabilis (22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
(27 reference statements)
1
3
0
Order By: Relevance
“…The prevalence of Salmonella species in smoked fish in Akwa Ibom State (Nigeria) confirmed this research result. This finding agrees with [21], which reported a prevalence of Salmonella Typhimurium and Salmonella Paratyphi from horse mackle with their respective percentages of 1.83 % and 1.52 %. The findings from this study also agree with [22] report, which recorded 20 % and 6.7 % of Salmonella Rubislam and Salmonella Senegal from Mullet fish samples and 13.3 % of Salmonella Senegal from Catfish.…”
Section: Qualitative Data-detection Of Salmonella Speciessupporting
confidence: 92%
See 1 more Smart Citation
“…The prevalence of Salmonella species in smoked fish in Akwa Ibom State (Nigeria) confirmed this research result. This finding agrees with [21], which reported a prevalence of Salmonella Typhimurium and Salmonella Paratyphi from horse mackle with their respective percentages of 1.83 % and 1.52 %. The findings from this study also agree with [22] report, which recorded 20 % and 6.7 % of Salmonella Rubislam and Salmonella Senegal from Mullet fish samples and 13.3 % of Salmonella Senegal from Catfish.…”
Section: Qualitative Data-detection Of Salmonella Speciessupporting
confidence: 92%
“…Also, the covering of smoked fish with paper could generate heat that would influence the growth of bacteria. Results from [38] and [21] indicated that, microbial contamination had been found in smoked fish due to unhygienic practices during processing, packaging, storage, poor environmental condition, and handling activities practiced by sellers and buyers contribute to the contamination of fishes. However, this study recorded a higher percentage (63 %) of buyers touching the fish with their bare hand without disinfecting their hand, and this could cause cross-contamination from the buyers.…”
Section: Mode Of Storage and Handlingmentioning
confidence: 99%
“…The highest prevalence of Aeromonas hydrophila was observed in fish (19.5%), followed by shrimp (9.2%), lobster (9.3%), and crab (6.7%) caught off the south coast of Iran, in which 57 strains out of 62 (91.9%) harbored the cytolytic enterotoxin gene (Rahimi et al, 2014). The prevalence of Citrobacter (45.56%), Proteus (31.79%), E. coli (7.64%), Shigella (7.64%), Salmonella (3.35%), Klebsiella (2.44%), and Enterobacter (1.52%) in horse mackerel (Trachurus trachurus) sold in Istanbul, Turkey was annually recorded (Tosun et al, 2016). All 20 seafood samples from landing centers and retail markets in Mumbai, India were contaminated with fecal coliforms ranging in number from 150 to 1.1 × 10 3 CFU/100 g. Among 329 isolates of E. coli, 175 isolates (53.19%) harbored virulence genes such as Shiga toxin 1 (stx1), Shiga toxin 2 (stx2), intimin (eaeA), and hemolysin (hlyA) (Prabhakar et al, 2017).…”
Section: Species Identification Based On the Vitek 2 Systemmentioning
confidence: 99%
“…Atlantic horse mackerel is a popular commercial fish in public markets. It is very popular for consumers in Turkey, Spain, and North African countries, having an annual catching value of 12,213.2 tons ( Ab Rahman et al , 2015 ; Tosun et al , 2016 ; Balami et al , 2019 ). Moreover, it is considered a migratory fish species that is indigenous to the Mediterranean, and Black Sea ( Abaunza et al , 2008 ; Aksissou and Casal, 2013 ).…”
Section: Introductionmentioning
confidence: 99%